Antioxidant, anti-inflammatory, and antiproliferative activities of aqueous extract from Calamintha nepeta L. leaves - Nadia Salhi; Hamza El Finou; Hicham Mohti; Zine el Abidin Saibari; Virginie Bito; Abdelhamid Zaid; Lhoussaine El Rhaffari (Scientific African)
Calamintha nepeta L. (Lamiaceae) is traditionally used in Morocco for its medicinal properties such as inflammation disorders. The current study aims to investigate the antioxidant, anti-inflammatory, and antiproliferative activities of aqueous extract from Calamintha nepeta L. leaves. Antioxidant properties were assessed in vitro through the scavenging activities of DPPH and ABTS radicals, along with ferric-reducing antioxidant power assays. Anti-inflammatory potential was examined on BV2 microglial cells, by determining the efficacy of the extract in reducing nitric oxide (NO) production in lipopolysaccharide (LPS)-activated microglial cells. In addition, anti-proliferative properties were tested on the A431 skin cancer cell line. HPLC analysis revealed the presence of compounds with potent anti-cancer properties, including cinnamic acid (1.2 %), rosmarinic acid (4.8 %), quercetin (21.1 %), and caffeic acid (8.3 %). The aqueous extract showed potent antioxidant activity with an IC50 of 28.1 ± 0.5 µg/mL for DPPH, an IC50 of 10.0 ± 0.1 µg/mL for ABTS, and 108.5 ± 2.4 mmol TE/100 g dw for FRAP. Significant anti-inflammatory activity was also demonstrated, inducing significant inhibition of NO production at the concentration of 1 mg/mL without influencing cell viability. It also exerted a significant antiproliferative action on A431 cancer cells at concentrations of 250 µg/mL and above. The cytotoxic effect was dose-dependent, with an IC50 of 360.7 ± 14.4 µg/mL.In conclusion, the aqueous extract of Calamintha nepeta L. leaves displays significant antioxidant properties, anti-inflammatory activity, and a promising cytotoxic effect against A431 cancer cells.